2001
DOI: 10.1016/s0378-1097(01)00230-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhodobacter capsulatus nifA mutants mediating nif gene expression in the presence of ammonium

Abstract: Expression of nitrogen fixation genes in Rhodobacter capsulatus is repressed by ammonium at different regulatory levels including an NtrC-independent mechanism controlling NifA activity. In contrast to R. capsulatus NifA, heterologous NifA proteins of Klebsiella pneumoniae and Rhizobium meliloti, respectively, were not subjected to this posttranslational ammonium control in R. capsulatus. The characterization of ammonium-tolerant R. capsulatus NifA1 mutants indicated that the N-terminal domain of NifA was invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…In contrast to other diazotrophic organisms, R. capsulatus contains two NifA proteins, NifA1 and NifA2, which differ only in their 19 N-terminal amino acid residues (26,54). These NifA proteins can substitute for each other to activate transcription of all the other nif genes under nitrogen-limiting conditions (47).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to other diazotrophic organisms, R. capsulatus contains two NifA proteins, NifA1 and NifA2, which differ only in their 19 N-terminal amino acid residues (26,54). These NifA proteins can substitute for each other to activate transcription of all the other nif genes under nitrogen-limiting conditions (47).…”
Section: Resultsmentioning
confidence: 99%
“…1a). For this purpose, cells were cultured under nitrogenasederepressing (2N) or -repressing (+N) conditions prior to protein extraction and Western analysis using a NifA1-specific antiserum raised against a synthetic oligopeptide corresponding to the N-terminal 17 amino acid residues (Paschen et al, 2001). In the wild-type strain, NifA1 accumulated only in N-limited cells, which is consistent with NtrC-mediated transcriptional control of the nifA1 gene (Fig.…”
Section: Ammonium-dependent Regulation Of Nifa Expressionmentioning
confidence: 99%
“…Previous studies demonstrated that constitutive (NtrCindependent) expression of nifA1 leads to a high-level accumulation of the NifA1 protein in both the absence and the presence of ammonium, but NifA1-mediated nifH transcription was still inhibited by ammonium (Paschen et al, 2001). To further analyse the roles of GlnB and GlnK in this post-translational ammonium control of NifA activity, we examined the same protein extracts which were prepared for the NifA1 detection (Fig.…”
Section: Post-translational Ammonium Control Of Nifa Activitymentioning
confidence: 99%
See 2 more Smart Citations